Management of median arcuate ligament syndrome - Mohit K. Manchella, BS; Vincent Wu, MD; Anahita Dua, MBChB, MD, MS, MBA, FACS (Journal of Vascular Surgery Cases and Innovative Techniques)
Median arcuate ligament syndrome (MALS) is a diagnostically challenging vascular compression disorder resulting from external compression of the celiac artery by the diaphragmatic crura. We report a unique case of a 51-year-old woman who developed multiple visceral aneurysms involving the pancreaticoduodenal arcade, attributed to hemodynamic stress from chronic celiac artery occlusion owing to MALS-related compression. This case underscores the importance of early recognition and intervention in MALS to prevent serious downstream complications, including aneurysm formation and potentially life-threatening hepatic or mesenteric ischemia.